Do Monetary Reward and Job Satisfaction Influence Employee Performance? Evidence from Malaysia - Mak, Met; Ibrahim, Ali; Juhary, Ali (EJBSS, 2015)
This quantitative study investigated the direct effect of monetary effect of job satisfaction on the relationship between monetary motivation on employees’ job performance and mediating motivation and employees’ job performance at oil and gas offshore production facilities in Malaysia. Data were collected using self administered survey questionnaire from convenience-sampled 341 employees of selected oil and gas companies in Malaysia. Data analyses were performed using the Statistical Product and Service Solution 21. The results of regression analysis and Sobel’s calculation showed that, at the .05 level, there was a significant direct effect of monetary motivation on employees’ job performance, and job satisfaction partially mediated the relationship between monetary motivation and employees’ job performance. The results of this study could assist employers and human resource managers in the development and implementation of their remuneration policy and strategy.